How E-Learning Deals with Higher Education during the Pandemic in Indonesia - Andhi Dwi Nugroho (English Education Department, 2020)
AbstractThe purpose of this study is to investigate the obstacles of e-learning, especially for students, and to find out students' perception in facing e-learning during coronavirus disease pandemic (covid-19). The rapid spread of coronavirus urges universities on a world-wide scale to do e-learning, including universities in Indonesia. This study uses online interviews and questionnaires to obtain the data, and descriptive qualitative method is used to analyse the data. The respondents in this study are 126 students with different majors from 21 universities in all across Indonesia, consisting of 6 state universities and 15 private ones. The results of the study reveal that e-learning has been carried out by universities in the country. It also shows there are several aspects such as the availability of online learning facilities, the use of facilities, learning processes, and some more points that need to reconsider or to optimize conducting the e-learning for the long term.Keywords: e-learning; students; pandemic